Drag-Reduction Performance Evaluation of Controllable Hybrid Steering Drilling System. (20th March 2021) - Zou, Jianyan; Chen, Ping; Ma, Tianshou; Liu, Yang; Wang, Xingming
Abstract : The excessive drag/torque and the backing pressure is an important factor that restricts the improvement of the penetration rate and the extension of the drilling in the sliding drilling process of extended-reach wells and horizontal wells. To deal with this problem, this paper developed a novel controllable hybrid steering drilling system (CHSDS) based on the friction-reducing principle of a rotating drill string. The CHSDS is composed of a gear clutch, hydraulic system, and measurement and control system. By controlling the meshing and separation of the clutch with the mud pulse signal, the CHSDS has two working states, which leads to two boundary conditions. Combined with the stiff-string drag torque model, the effects of the drilling parameters on the friction-reducing performance of the CHSDS are analyzed systematically. The results show that the friction reduction effect in the inclined section is the most significant, followed by that in the horizontal section, whereas there is almost no impact in the vertical section. Friction reduction increases with the rotary speed and the drilling fluid density, whereas it decreases with the increase in the surface weight-on-bit and the bit reaction torque. Field tests confirm the separation and meshing function of the CHSDS. The developed controllable hybrid steering and friction-reducing technology provides an alternative approach for the safe and high-efficiency drilling of horizontal wells.